ACUTE DIARRHEA - Irshad ul Haq (Journal of University Medical & Dental College, 2020)
Acute diarrhea is a major public health problem in both resource-limited countries like Pakistan and developed countries of the world.1,2,6 In the former acute diarrhea is the second highest cause of death (after pneumonia) in children under five, and it is likely that repeated enteric infections may be responsible for both growth and mental retardation in a sizeable number of children.